Sanksi Tindak Pidana Pelaku Deelneming Pembunuhan Berencana Terhadap Anak di Pengadilan Negeri Denpasar - Azalia Elian Faustina; Martoyo Martoyo (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2022)
Participation Murder (Delneeming) is a murder that contains various forms of physical or non-physical involvement of a person or group in carrying out a behavior or activity that creates a criminal act. However, in this case, problems often arise regarding accompaniment homicide, especially in court when judges consider the issue of accompaniment homicide from the point of view of the Criminal Law Act. The focus of the problems studied in this study are: 1.) How is the case for the perpetrators of deelneming/involvement of premeditated murder against children in the decision Number 864/PID.B-2015.PN.DPS at the Denpasar Bali District Court? 2.) Ratio Decidendi in the case of the crime of premeditated murder against children in decision number 864/PID.B-2015.PN DPS at the Denpasar Bali District Court 3.) Legal consequences for the establishment of sanctions for perpetrators of premeditated murder against children in decision number 864/ PID.B-2015.PN DPS at the Denpasar Bali District Court. The results of this study include: 1.) The chronology of the motive for assisting the murder carried out by Agustay as the defendant to the victim Angeline with the excuse of helping the main perpetrator Margarieth in exchange for a gift and hiding the problem from anyone. 2.) There is a judge's legal consideration which states that the defendant's brother was sentenced to 10 years in prison for the consideration of helping premeditated murder and burying the body with the intention of concealing the death 3.) In the legal consequences there is the formation of sanctions by the judge which contains irrelevant between the Indonesian judicial system and regulations the applicable legislation, among others, the decisions by the panel of judges and the regulations contained in article 57 of the Criminal Code and the absence of legal certainty because from a logical point of view there is a conflict with legal norms that can cause problems.